Structural, kinetic, and pharmacodynamic mechanisms of D-amino acid oxidase inhibition by small molecules - Hopkins, Seth C; Heffernan, Michele L R; Saraswat, Lakshmi D; Bowen, Carrie A; Melnick, Laurence; Hardy, Larry W; Orsini, Michael A; Allen, Michael S; Koch, Patrick; Spear, Kerry L; Foglesong, Robert J; Soukri, Mustapha; et al. (Journal of medicinal chemistry, 2013)
We characterized the mechanism and pharmacodynamics of five structurally distinct inhibitors of d-amino acid oxidase. All inhibitors bound the oxidized form of human enzyme with affinity slightly higher than that of benzoate (Kd ≈ 2-4 μM). Stopped-flow experiments showed that pyrrole-based inhibitors possessed high affinity (Kd ≈ 100-200 nM) and slow release kinetics (k < 0.01 s(-1)) in the presence of substrate, while inhibitors with pendent aromatic groups altered conformations of the active site lid, as evidenced by X-ray crystallography, and showed slower kinetics of association. Rigid bioisosteres of benzoic acid induced a closed-lid conformation, had slower release in the presence of substrate, and were more potent than benzoate. Steady-state d-serine concentrations were described in a PK/PD model, and competition for d-serine sites on NMDA receptors was demonstrated in vivo. DAAO inhibition increased the spatiotemporal influence of glial-derived d-serine, suggesting localized effects on neuronal circuits where DAAO can exert a neuromodulatory role.